(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The presented research sheds light on the topic of breidolia and the reflection of its intellectual vision on the formation of new formal patterns that the designer can employ in graphic design. it is consedered an art that enters various fields of life and is directly related to its accelerating reality. It is an art that reflects different fields that affect and affected by the recipient. The breidolia phenomenon has a role in crystallizing visual perceptual skills in seeing new formal patterns derived from activating this perception, stimulating the imagination with its mental images.The transforming the illusion achieved from visual images, which may be confused and irregular, into new perceptible forms that achieve visual communication with the recipient. This reflects the goal of Completed graphic design idea.This is what the research seeks to achieve its goal represented in revealing the phenomenon of (pareidolia) and its reflection on graphic design, which came out with a set of results. Most notably that in the variations of graphic designs, the designer employs formal patterns that are not clear and vague to the recipient. That understanding for these patterns is interpreted through The phenomenon of (pareidolia). It helps in determining the effects of these formal designs on the various levels of awareness and perception, which contributes to showing how to interact with the new visual form, and to what extent the change in its form does not affect the meaning and content of the graphic design and the understanding of the content of its design idea.